A representative volume element model for ultra-high-molecular-weight-polyethylene composites. (15th April 2021) - Kempesis, D.; Iannucci, L.; Rosso, S. Del; Curtis, P.T.; Pope, D.; Duke, P.W.
Abstract: This paper presents the development of a Representative Volume Element (RVE) for Ultra-high-Molecular-Weight-Polyethylene (UHMWPE) composites. The numerical models were based on the fibrillar nature of UHMWPE fibres, which consist of smaller scale, continuous through-the-length macro-fibrils. A three-dimensional constitutive model for UHMWPE macro-fibrils was developed and implemented in the LS-DYNA explicit finite element (FE) code, through a user-defined subroutine. The proposed transversely isotropic model accounts for viscoelastic effects in the principal direction of the fibre coupled with the continuum damage mechanics approach. Energy dissipation associated with failure was controlled through an objectivity algorithm to provide mesh insensitive solutions. Hill's yield criterion was used to capture the non-linear response of the fibre in the transverse direction. The RVE was built from macro-fibrils and a Thermoplastic Polyurethane (TPU) resin in order to study the micromechanical response of the polymeric composite laminate. Periodic boundary conditions (PBC) were imposed in the model and a penalty-based cohesive contact algorithm was used to simulate interfibrillar interactions and the interface between the macro-fibrils and the resin. The proposed RVE model provides insight on microscale deformation mechanisms in UHMWPE composites under different loading conditions.